Estimated production and evapotranspiration of irrigated bean cultivars - Márcio J. de Santana; Leandro B. Lemos; Stefany S. de Souza; Talita M. Campos; Flávia M. da Silva; Rafael D. Borges (Engenharia Agrícola, 2014)
The current study intended to determine the optimum water depth, yield and evapotranspiration (ETc) for bean cultivars. The experiment was conducted in the Campus of Unit I of the Triângulo Mineiro Federal Education and Technology Institute in Uberaba, MG, in a completely randomized design with three replications. The treatments consisted of four water-replacing levels in the soil (70, 100, 130 and 160% of the crop evapotranspiration) and four bean cultivars (Pérola, BRSMG Madrepérola, BRSMG Majestoso and IAC Alvorada). The average values of ETc obtained for soil water balance for the cultivars Pérola, BRSMG Madrepérola, BRSMG Majestoso and IAC Alvorada were, respectively, of 5.25 mm day-1, 4.59 mm day-1, 4.54 mm day-1 and 4.77 mm day-1. The water depths which provided the highest yields were for the cultivars Pérola, BRSMG Madrepérola, BRSMG Majestoso and IAC Alvorada of 451.61 mm, 454.41 mm, 504.71 mm and 344.30 mm, respectively. The maximum yields found were 4597.87 kg ha-1 (Pérola), 4546.27 kg ha-1 (BRSMG Madrepérola), 4253.39 kg ha-1 (BRSMG Majestoso) and 3958.50kg ha-1 (IAC Alvorada).